Analisis Keberhasilan Implementasi Model Pembelajaran Berbasis Proyek dalam Pembelajaran Matematika Tingkat Perguruan Tinggi - Yenny Anggreini Sarumaha; Al Ikhlas; Rendi Hadian A. Tamagola; Hetty Elfina; Singgih Prastawa; Joni Wilson Sitopu (Departement of Mathematics Education, 2024)
This study aims to analyse the successful implementation of project-based learning model in mathematics learning at university level. Literature studies and field observations were conducted to evaluate the implementation of project-based learning models in several higher education institutions. The results showed that the implementation of project-based learning model in mathematics learning in higher education has positive impacts, among others: 1) increasing students‘ active involvement and motivation in the learning process, 2) developing mathematical competence, critical thinking skills, and other 21st century skills, 3) encouraging meaningful and contextualised learning, and 4) improving students’ collaboration and communication skills. However, there are some challenges in its implementation, such as: lecturer readiness, resource availability, and curriculum adjustment. The implication of the results of this study is the need for innovative mathematics curriculum development, increased lecturer competence, and adequate institutional support to optimise the implementation of project-based learning in higher education. This study provides valuable insights for mathematics education practitioners in designing and implementing student-centred learning oriented towards the development of 21st century competencies.